Hydrocephalus and Shunt Infections - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
In the 10-year period, 1973-82, 431 children underwent cerebrospinal fluid shunt insertion for hydrocephalus at Children's Memorial Hospital, Chicago.